(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2025)
In this article, I reflect on my experience of working alongside community activists trying to support community health and multi-directional integration in Cables Wynd House (‘the Banana Flats’), Leith, and how its reputation in the city may have presented difficulties. I bring together insights from Community Development, Migration Studies and other disciplines, as well as reflections on my own practice, and suggest a model for working towards community health and multi-directional integration in neighbourhoods on the receiving end of area-based stigma.